2020
DOI: 10.1111/vox.12934
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on consumer information in transfusion. A qualitative study of consumers and prescribers

Abstract: Background and objectives Fresh blood product transfusion requires patient education for fully informed consent, and written consumer information is frequently used. Few studies have examined consumer preferences regarding written and verbal transfusion information provided. As a qualitative study, this research was designed to explore participant understanding and by analysing and integrating themes, generate a model to understand how transfusion information should be developed and used in practice. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Liao et al shared this sentiment and undertook a qualitative study of health professionals and patients perceptions of informed consent [25]. They sought to understand how patients perceive the current resources available to them that aid in giving information on risks and how they would prefer to receive that information [25]. Interestingly, they found a similar trend to our study where patients tended to rely upon, and trust, doctors recommendations, as they feel too overwhelmed to make informed decisions [25].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Liao et al shared this sentiment and undertook a qualitative study of health professionals and patients perceptions of informed consent [25]. They sought to understand how patients perceive the current resources available to them that aid in giving information on risks and how they would prefer to receive that information [25]. Interestingly, they found a similar trend to our study where patients tended to rely upon, and trust, doctors recommendations, as they feel too overwhelmed to make informed decisions [25].…”
Section: Discussionsupporting
confidence: 59%
“…In the context of PBM literature, the inclusion of patients in intervention development has tended to be tokenistic, with consumer consultation and feedback usually only sought after the development of an intervention (e.g. patient information or policy) [24,25]. Liao et al shared this sentiment and undertook a qualitative study of health professionals and patients perceptions of informed consent [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that neither prescribers 22 In the context of PBM literature, the inclusion of patients in intervention development has tended to be tokenistic, with consumer consultation and feedback usually only sought after the development of an intervention (for example, patient information or policy). 23,24 Liao et al shared this sentiment and undertook a qualitative study of health professionals and patients perceptions of informed consent, 24 seeking to understand how patients perceive current resources available to them that provide information on risks, and how they would prefer to receive that information. 24 Interestingly, they found a similar trend to our study where patients tended to rely upon, and trust, doctors recommendations, as they feel too overwhelmed to make informed decisions.…”
Section: Discussionmentioning
confidence: 99%